Neuromodulation of choice-induced preference changes: the tDCS study of cognitive dissonance - Rybina, Elena; Colosio, Marco; Shestakova, Anna; Klucharev, Vasily (Frontiers in Psychology, 2023)
Difficult choices between two equally attractive options occur with a conflict inducing psychological tension that is known as cognitive dissonance. Cognitive dissonance could lead to changes in the desirability of options: the chosen option becomes more desirable, whereas the rejected option is devalued. Neural mechanisms of such choice-induced preference changes are not fully understood. In this study, we used transcranial direct current stimulation (tDCS) to modulate the activity of the posterior medial frontal cortex (pMFC), which has been associated with choice-induced preference changes in neuroimaging studies. Prior to a revised version of Brehm's free-choice paradigm, participants underwent cathodal (versus sham) or anodal (versus sham) tDCS of the pMFC. Our results showed that cathodal tDCS significantly decreased the choice-induced preference change relative to a sham (placebo) stimulation, but only in direct comparisons of rejected options. No significant effect of anodal tDCS in comparison with sham was observed. Overall, these results partially support the theory about the contribution of the pMFC in choice-related cognitive dissonance and subsequent changes of preference.Contrary to the assumptions of normative economic theory, choice preferences are not only driven by our attitudes but also modulated by the experience of previous choices. Brehm 's study (1956) suggested that, after choosing between two similarly attractive options, individuals no longer perceive these options as similar, evaluating the chosen option more positively and devaluating the unchosen option. The devaluation of the rejected option has been repeatedly demonstrated in studies using different versions of "free choice paradigm" (Colosio, Shestakova, Nikulin, Blagovechtchenski, &Neuromodulation of choice-induced preference changes 2